Using New Venture Competitions to Link the Library and Business Students - Li, Yanli (Qualitative and Quantitative Methods in Libraries, 2016)
New venture competitions are designed to motivate university students to develop business plans and to present them to a panel of judges including business community members. Wilfrid Laurier University has integrated the new venture competition into its business school curriculum. This paper intends to share the experience of a new business librarian at Laurier Library in working with faculty to assist students to prepare for the new venture competition. A short survey is conducted to evaluate how students use the library resources and services for completing their projects. The results show that course guides and databases are the most used library resources. Marketline, Passport and Financial Performance Data are three databases found most useful by the students. Expectations of the liaison librarian include creating a tailored guide for the competition, delivering instruction sessions and providing research consultation on a continuing basis. It is critical to build close partnerships with faculty and to provide tailored services after fully assessing students’ needs.